Integrating Human Rights into Development : Donor Approaches, Experiences, and Challenges, 2nd ed. - World Bank; Organisation for Economic Co-operation and Development (World Bank and OECD, Washington, DC, 2013)
The past two decades have witnessed a convergence between human rights and development, particularly at the level of international political statements and policy commitments. This phenomenon is captured in milestones such as the 2007 OECD DAC Action Oriented Policy Paper on Human Rights and Development (“AOPP”), the 2010 UN World Summit Outcome Document, the commitments of the 2005 and 2011 High-Level For an Aid Effectiveness in Accra and Busan. The connections between rights violations, poverty, exclusion, environmental degradation, vulnerability and conflict continue to be explored and better understood. More positively, there is growing recognition of the intrinsic importance of human rights in a range of contexts, as well as their potential instrumental relevance for improving development processes and outcomes.